МОРФОЛОГО-АНАТОМІЧНА БУДОВА ТРАВИ ВЕРОНІКИ ЛІКАРСЬКОЇ (VERONICA OFFICINALIS L.) - Марчишин, С. М.; Мілян, І. І.; Сіра, Л. М. (Фармацевтичний часопис, 2015)
MORPHOLOGICAL AND ANATOMICAL STRUCTURE OF HERB VERONICA OFFICINALIS (VERONICA OFFICINALIS L.) S.M. Marchyshyn, I.I. Milian SHEI "Ternopil State I.Ya.HorbachevckyiMedicalUniversityof Ministry of Public Health ofUkraine" Veronica officinalis - a perennial herb 10-30 cm long, with clambering, branched stem at the base, which forms a timber. Stems are covered with dense short hairs. Leaves narrow into short petiole, inverse-ovate, dentate- serrated, slightly rough. Multifloral, flowering clusters grow from one bosom of two opposite leaves. The flowers are pale blue with a purple tinge, rarely white. The plant has astringent taste, fresh - without odor, dried - has a pleasant smell. It flowers in June - August. Botanics refer Veronica officinalis to the family of Plantaginaceae (Scrophulariaceae), but its family is called veronica’s because there are so much Veronica’s species in the world. Microscopic analysis of grass Veronica officinalis L. Stem. The cross sections is round, uniformly pubescent. External walls of epidermal cells with finely cuticle, stomata and little rosettes opaque multicellular hairs. Beamless anatomical structure is clearly separated by a narrow ring of the central cylinder. On the preparations with basic surface epidermis stem cells with thin, straight side walls, slanted and radial thickened, warted outer shells. Basic cells occur between small and big oval idioblasts with clear content. Occasionally narrow oval anomocytic stomata complexes, surrounded by 4-5 cells are observed. Simple and glandular trichomes are placed evenly, but not densely. Simple hairs are narrow, elongated, uniseriate, multicellular, slightly elevated with sharp shape formed 6-8 straight-walled, square-rounded cells. Leaves. The cells of the upper and lower epidermis of medium size, thin or thick beaded, more or less winding side walls and moderately thick outside, covered with soft folded cuticle membranes. Epidermal cells of veins elongated, shell straight or slightly wavy, with small bulges and chotkopodibnymy folded cuticle. Stomata spherical-oval, anomocytic, they are more in the lower epidermis. Simple and glandular trichomes the structure are the same as on the stems and sepals. Leaf blade is thin, dorsoventral, mesophillous clearly differentiated, moderately layered, with an average rate of palisadity. Columnar single layer clorenchyma has wide cells, accumulating phenolic compounds. Sponge mesophillous is 3-4 layer. The main vein and lateral veins of first order are thin, with a parenchyma facing, which contains phenolic compounds and thin, mostly ladder-shaped and porous tracheids and vessels. Phloem is accompanied sclerenchyma cord.Its short petoole has triangular shape, a leading system consists of one central and two lateral small vascular bundles. Perianth parts. Sepals are more hairy on the edge with typical for other parts simple hairs and glandular specific trichomes. they cover The base of leaves is covered abundantly, with one or two-cell yellow oval heads and a long two- or three-cell which is usually bent in arc-like way. Epidermal cells are with longitudinal folds cuticle. Conclusion. Morphological and anatomical characteristics of grass Veronica officinalis L. and the main morphological and anatomical structural diagnostic features of its stems, leaves, perianth are studies, what will be used in the design of quality control methodology " herb Veronica оfficinalis”.